Coherent synchrotron radiation wake expressions with two bending magnets and simulation results for a multiturn energy-recovery linac - W. Lou; G. H. Hoffstaetter (Physical Review Accelerators and Beams, 2020)
This paper consists of two main parts regarding coherent synchrotron radiation (CSR). The first part extends the CSR theory of two particle interaction from a system of one bending magnet to two bending magnets, where the wake can leak from the first to the second. The new theory agrees well with the established simulation code Bmad. The second part of the paper presents the CSR simulation results on CBETA, the Cornell BNL Energy-Recovery-Linac (ERL) Test Accelerator, in which the magnets are so close to each other and the new extended theory becomes important. CBETA is the first multiturn ERL with superconducting radio frequency (SRF) accelerating cavities and a Fixed Field Alternating gradient (FFA) beamline. Simulations show that CSR causes phase space dilution that becomes more significant as the bunch charge and the number of recirculation passes increase. Potential ways to mitigate the CSR effects, including adding vacuum chamber shielding and increasing bunch length, are being investigated.